Colostrum quality and the neonatal calf nutrition and growth with or without a source of PUFA supplement: Colostrum quality and PUFA supplements to calf - H B, Veeresh; Bandla, Srinivas (Indian Journal of Dairy Science, 2025)
The calf acquires immunity from the colostrum only after birth, which protects for a few weeks but developing innate immunity after birth is essential for its lifetime performance. The present study aimed to supplement Flaxseed oil (FSO) in neonatal calves as polyunsaturated fatty acids (PUFA) source. Twenty male and female Deoni calves were randomly distributed into four groups where a group of male (TGM) and female (TGF) calves were drenched with FSO daily from day 6 to 28 and compared with control; CGM, and CGF. After that, a bolus consisting of ground flaxseed was fed till 90 d besides mixed green fodder and concentrate mixture. Digestibility trial in neonates was carried out by indirect method. The colostrum quality or immunoglobulins (Ig) were reduced from 93 to 39 mg/mL on the second day. The total diet CP in neonatal age was 22%, and digestible CP was 13.2%. It was 18% and 9%, respectively, during preweaning. Weight gain in the male calves was higher than in the female calves, although their intake was statistically comparable. The weight gain in the TG was significant until the first fortnight and subsequently comparable, but the relative risk of disease in males and females of CG was 6.57 folds more than TG (P< 0.001). The study concluded that the FSO supplementation at neonatal age followed by supplementing ground flaxseed as bolus had no adverse influence on the diet intake, digestibility of nutrients, and energy balance. The marginal improvement in weight gains and reduced disease risk prompts the recommendation of the supplement/drench FSO 30 mL/d for neonatal calves.